Rigid, Variable-View Endoscope in Neurosurgery: First Intraoperative Experience. (August 2015) - Ebner, Florian H.; Roser, Florian; Roder, Constantin; Tatagiba, Marcos; Schuhmann, Martin U.
Introduction . The endoscope became a highly valued visualization tool in neurosurgery. However, technical limitations caused by the rigidity of current standard endoscopes significantly decrease ergonomy in transcranial neurosurgery. Further technological developments will aid enlarging the surgical applicability. Objective . To evaluate the intraoperative features of a rigid variable-view endoscope in neurosurgery. Methods . We assessed a 4 mm rigid rod lens endoscope (EndoCAMeleon, Karl Storz, Tuttlingen, Germany) in the intraoperative setting. The device offers a variable angle of view from 15° to 90° in one plane. The endoscope was used in 3 cases (aneurysm clipping, vestibular schwannoma surgery, endoscopic third ventriculostomy) for inspection. Results . Direct insertion of the device through the craniotomy/burr hole with the lowest angled view (15°) was always possible. Neurovascular structures crossing the access route could be visualized and avoided. This allowed a targeted positioning of the endoscope's tip in the operating field. Once the target point was reached, viewing direction was changed in one plane from 15° to 90° according to anatomic demands. As the endoscope's tip does not move while the lens is rotated, surrounding neurovascular structures are not at risk to be injured. However, turning of the lens-controlling wheel in proximity to delicate structures may be inconvenient. Conclusion . The rigid, variable-view endoscope has the potential to become an appreciated visualization tool in neuroendoscopy. The steerable lens enables a tremendous expansion of the visual field, resulting in higher efficiency for surgeons and increased safety for patients.